Critical Awareness within the Teachings of the Bhagvat Gita and the Aditya Jyoti Path - Sharma, Bikash (Panauti Journal, 2023)
Total ignorance of what we have had in the eastern body of knowledge and civilization for a long period of time may lead ones to imperfect course of learning since there have already been in the east what we claim today to be new and innovative. The concepts such as critical thinking and critical teaching – though they were not explicitly expressed in words – existed clearly in the literatures and practices of the ancient eastern life. In this brief review article an attempt is made to explore some kind of bridging up between the ancient eastern values and today’s (post) modern expressions related with criticalities in education, particularly in teachings. The concepts of critical discourse and critical pedagogy are elaborated, and a few of the contents of the two renowned books on eastern values are analyzed and interpreted putting the intensive curiosity on how these ancient eastern understandings throw insights on today’s critical framework of thinking. This article expects for the readers to have general background knowledge on the discourse related with the Mahabharata War in the times of Krishna and on the enriched guidelines given by Guru Aditya for ideal human life of the present time.